PENGEMBANGAN KOMIK BERBASIS LITERASI SAINS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SEKOLAH DASAR - Risma Widianto; Sri Cacik (ELENOR: Elementary School Journal, 2023)
Abstract. This study aims to develop scientific literacy-based comics on material changes in the form of objects to determine the level of validity, practicality and effectiveness of the product being developed. The development model used is ADDIE which consists of 5 stages, namely analyze, design, develop, implement, evaluate. The instruments used were interviews, validation of material experts, media experts, linguists, implementation of learning, student response questionnaires and student learning outcomes tests. The results of the validation test showed that the scientific literacy-based comics developed had very valid criteria with a percentage of material experts 92 %, media experts 94%, and linguists 78%. The results of the analysis of the implementation of learning and student response questionnaires were obtained with very practical criteria with a percentage of 90% for the implementation of learning and 91% for student response questionnaires. And the results of student learning tests obtained an average N-Gain score of 0.83 with a percentage of 83.3% which indicates high effectiveness criteria. Based on the scores obtained, the comics developed are very valid, very practical and effective to use. Abstract. This study aims to develop scientific literacy-based comics on material changes in the form of objects to determine the level of validity, practicality and effectiveness of the product being developed. The development model used is ADDIE which consists of 5 stages, namely analyze, design, develop, implement, evaluate. The instruments used were interviews, validation of material experts, media experts, linguists, implementation of learning, student response questionnaires and student learning outcomes tests. The results of the validation test showed that the scientific literacy-based comics developed had very valid criteria with a percentage of material experts 92 %, media experts 94%, and linguists 78%. The results of the analysis of the implementation of learning and student response questionnaires were obtained with very practical criteria with a percentage of 90% for the implementation of learning and 91% for student response questionnaires. And the results of student learning tests obtained an average N-Gain score of 0.83 with a percentage of 83.3% which indicates high effectiveness criteria. Based on the scores obtained, the comics developed are very valid, very practical and effective to use.